Talking mental health - study protocol for a cluster-randomized controlled trial of mental health prevention in elementary schools in Germany - Peter, Sophia; Bednarz, Julia; Sommer, Paula; Taubner, Svenja (Frontiers in Psychology, 2026)
BackgroundMental disorders are highly prevalent, and mental health problems often start in childhood or adolescence. However, barriers to care, such as low mental health literacy and stigma, increase the risk of developing mental disorders. The abilities to recognize, talk about and seek help when mental health problems occur are important processes to overcome such barriers. The school-based prevention program “Talking mental health” (TMH) aims to reduce stigma among children in elementary schools and their families by increasing mental health literacy and help-seeking behavior.MethodsIn this study, the “Talking mental health” (TMH) prevention program is evaluated using a cluster-randomized design, comparing an intervention group with a waitlist control group. The primary outcomes are mental health literacy, stigma and help-seeking behavior. Measurement takes place pre and post, as well as at a six-week follow-up. The sample size aims for 35 school classes with approximately 525 parents and children. The study also examines the effects of an additional parent training on children’s and parents’ mental health.DiscussionIf effective, this study provides a validated prevention program to promote mental health in elementary schools, potentially allowing wider implementation. This could help families access existing support structures at an early stage, therefore preventing the chronic progression of mental health problems. The methodological and practical challenges of the study are discussed, as well as general challenges of school-based prevention efforts.Clinical trial registrationhttps://drks.de/search/en/trial/DRKS00035171, identifier DRKS00035171.